Avalanche dynamics in crumpled aluminum thin foils. (1st April 2015) - Abobaker, M.; Bouaziz, O.; Lebyodkin, M.; Lebedkina, T.; Shashkov, I.V.
Abstract : Uniaxial compression of crumpled aluminum thin foils with different relative densities was studied using an acoustic emission (AE) technique. The AE signal analysis reveals a power law linking the probable density and amplitudes of acoustic events, proving an avalanche dynamics of plastic deformation. The exponent found for the distributions of squared amplitudes that reflect the dissipated mechanical energy places the observed behavior among those found previously for bulk samples of various pure materials.